The impact of financing structure on bank profits : Applied research on a sample of commercial banks listed in the Iraq Stock Exchange for the period (2011-2020) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The research aims to identify the concept of financing structure and what are the determinants that affect it and the goals achieved by financing in commercial banks in addition to the sources upon which the financing structure depends consisting of internal financing sources and external financing sources and their connection to the profits of commercial banks. Baghdad, Khaleeji Commercial Bank) registered in the Iraq Stock Exchange during the period for the years (2011-2020) published in the Iraq Stock Exchange from and the research relied on financial analysis tools to analyze the independent variable the following financing structure (the ratio of equity to total assets, the ratio of deposits to Total liabilities, the ratio of loans to total liabilities (as well as the researcher’s use of financial ratios for profitability indicators (the ratio of the rate of return on assets (ROA), the ratio of the rate of return on equity (ROE), the ratio of the rate of return on investment (ROI)) depending on the financial statements Especially the balance sheets and income statements of those banks, and the researcher reached a set of conclusions and recommendations, the most important of which is that the funding structure depends on the trade-off between return and risk and the extent to which financial management prefers one of them, as the bank’s retention of high short-term financing rates compared to long-term financing leads to a decrease in the bank’s profitability due to the high interest Accordingly, the research achieved a set of recommendations, including the study recommends that banks develop effective diversification strategies for the financing structure between owned financing and borrowed financing in order to achieve a better or optimal mix between them, which makes the financing cost at its minimum and increases the profitability of the bank.